Effect of Urea-to-Fatty Acid Ratio and Crystallization Temperature on the Fatty Acid Composition of Rice Bran Oil Concentrate by Urea Complexation - Thammapat, Pornpisanu; Siriamornpun, Sirithon (Naresuan University Journal: Science and Technology (NUJST); Vol 31 No 1 (2023): January - March 2023DO - 10.14456/nujst.2023.3, 2022)
Processes for the production of polyunsaturated fatty acid (PUFA)concentrates have important because of the beneficial properties of these substances to human health and in functional foods. This study investigated the changes in different urea-to-fatty acid (U/FA) ratios (1:1, 2:1 and 3:1, w/w) and crystallization temperatures (-10, 0 and 10 o C) on the fatty acid composition of rice bran oil concentrate, compared with native rice bran oil (control). Overall, the amount of PUFA in the rice bran oil concentrate increased as U/FA ratios increased and crystallization temperature decreased, while saturated fatty acids (SFA) and monounsaturated fatty acids (MUFA) decreased. The results showed that the U/FA ratio at 3:1 had the highest PUFA (56%) among complexation treatments. The higher PUFA concentrations in low-temperature crystallization were obtained at -10 o C, with PUFA rising to 60.6%. Keywords: Polyunsaturated fatty acids, Rice bran oil concentrate, Urea inclusion, Crystallization temperature